Pengaruh Pemberian Pupuk Green Tonic dan Pupuk NPK Mutiara Terhadap Pertumbuhan Bibit Tanaman Kakao Forestero (Theobroma cacao L) - Ivan Wahyudi; Mahdalena Mahdalena; Hamidah Hamidah (Universitas Widya Gama Mahakam, 2018)
The Effect of Green Tonic Fertilizer and Pearl NPK Fertilizer on the Growth of Forestero Cocoa Plant Seeds (Theobroma cacao L) The aim of this study was to determine the effect of Green Tonic, NPK Mutiara and the extraction of Green Tonic and NPK Mutiara on cocoa seedling growth. This research was carried out at Gunung Panjang Samarinda Seberang East Borneo. with a time of ± 3 months, starting from April to July 2016. The design of the study used factorial randomized block design (RCBD) 4 x 4 with a number of replications 3 times, with factorial analysis. The treatment consists of 2 factors. The first factor is the administration of POC Green Tonic consisting of 4 levels, namely: p0: Without treatment, p1: 2 ml / 1 Liter of Green Tonic Concentration, p2: 3 ml / 1 Liter of Water Tonic Concentration, p3: 4 ml Green Tonic Concentration / 1 Liter of Water, The second factor was the administration of NPK Mutiara consisting of 4 levels, namely: v0: Without treatment, v1: Giving NPK Mutiara Fertilizer 50 grams / polybag, v2: Giving NPK Mutiara Fertilizer 100 grams / polybag, v3: Giving NPK Fertilizer Pearl 150 grams / polybag. From the analysis of variance showed that the effect of giving green tonic liquid organic fertilizer (P) was the best on the parameters of stem diameter of 30 DAP and 60 DAP of cocoa plants achieved by the treatment of p3 (4 ml / 1 Liter of Water Green Tonic Concentration), NPK Mutiara fertilizer (V) the best in the parameters of plant height 30 DAP, 60 DAP and 90 DAP, stem diameter 30 DAP and 90 DAP, number of leaf 60 DAP, leaf area 30 DAP cocoa plants achieved by v3 (Giving NPK Pearl Fertilizer 150 gram / polybag) while for stem diameter 60 DAP, number of leaves 30 DAP achieved by v1 (Giving NPK Mutiara Fertilizer 50 g / polybag), for the number of leaves 90 DAP, the area of Leaves 60 DAP and 90 DAP achieved by v2 (Giving NPK Pearl Fertilizer 100 g / polybag), The best interaction of POC green tonic and NPK pearl (PV) fertilizer on stem diameter parameters 30 DAP and 60 DAP, number of leaves of 90 DAP, leaf area of 60 DAP and 90 DAP was achieved by p3v2 (4 ml / 1 Liter Water + Green Tonic Concentration Pearl NPK fertilizer 100 grams / polybag. The difference for 30 HST leaf area is achieved by p1v3 (2 Ton / 1 Liter Water + Green Tonic Concentration + 150 gram Pearl NPK Fertilizer / polybag).